4-Methylbenzohydrazidato-kappa N-2 `,O)[2-(4-methylbenzoylhydrazinylidene-kappa N-2,O)-3-phenylpropionato(2-)]oxidovanadium(V) methanol monosolvate - Wong, H.W.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The V V atom in the title compound, [V(C8H9N2O)(C17H14N2O3) O]center dot CH3OH, is N,O-chelated by the benzoylhydrazidate anion and O,N,O'-chelated by the (benzoylhydrazono)propionate dianion. The octahedral trans-N2O4 coordination geometry is completed by the vanadyl O atom. Two mononuclear complexes and two solvent molecules are linked by O-H center dot center dot center dot O and O-H center dot center dot center dot N hydrogen bonds, generating a centrosymmetric aggregate.